Diseño de plan estratégico para el “hostal solar del puerto” de la ciudad de Machala, provincia de El Oro. - Prieto Valverde, Maria Jose (My University, 2020)
This work is aimed at the hotel sector in the province of El Oro and national and foreign tourists. The case study is the design of a strategic plan for the Hostal Solar del Puerto, located in the parish of Puerto Bolívar in the city of Machala. Through strategic planning, this work aims to design a strategic plan for the “Solar Hostel of the Port” of the city of Machala, province of El Oro, through marketing strategies, which will serve to create competitive advantage and activate tourism in the city and the province. The methodology to be used is qualitative based on documentary and bibliographic review of scientific articles. As a result we have that the company Hostal Solar del Puerto, should strengthen its customer service attention through training staff in hospitality and tourism, demand support to the sectional and shift governments to promote tourism, and make strategic alliances with operators Tourists of the city and the country.
El presente trabajo está dirigido al sector hotelero de la provincia de El Oro y a turistas nacionales y extranjeros. El caso de estudio es el diseño de un plan estratégico para el Hostal Solar del Puerto, ubicado en la parroquia de Puerto Bolívar de la ciudad de Machala. Mediante la planificación estratégica este trabajo tiene como objetivo, diseño de plan estratégico para el “Hostal Solar del Puerto” de la ciudad de Machala, provincia de El Oro realizar, mediante estrategias de marketing, que servirán para crear ventaja competitiva y activar el turismo en la ciudad y la provincia. La metodología a utilizar es cualitativa basado en revisión documental y bibliográfica de artículos científicos. Como resultado tenemos que La empresa Hostal Solar del Puerto, debe fortalecer su atención del servicio al cliente mediante capacitación al personal en cuanto a hoteleria y turismo, exigir apoyo a los gobiernos seccionales y de turno para fomentar el turismo, y realizar alianzas estratégicas con operadores turísticos de la ciudad y el país.
Keywords: PLAN ESTRATÉGICO; SECTOR HOTELERO; HOSTAL SOLAR DEL PUERTO; TURISMO